Implementation Agreement By Mixed Marriage Based On Act No. 1 of 1974 Concerning Marriage After Constitutional Court Ruling No. 69 / PUU-XIII / 2015 (Study of Notary Role) - Riyanto Riyanto; Wachid Aryanto; Arief Cholil (Jurnal Akta, 2018)
Abstract. The bride and groom's candidate before the marriage takes place, can make a "Marriage Agreement" to provide legal certainty related to property and for legal protection against third parties. Primarily for mixed marriages, the bride and groom are subject to two different legal systems according to their nationality. , the agreement made by the Marriage Agreement has been amended by the Decision of the Constitutional Court Number: 69 / PUU-XIII / 2015 dated October 27, 2016. The positive implication for the intermarriage is that it can have land rights in the form of Ownership Rights (HM) and Right to Build (HGB) without having to divorce first. Then, this research intends to discuss the practice of the Implementation of Mixed Marriage Agreements based on Act No. 1 of 1974 concerning Marriage after the decision of the Constitutional Court Number: 69 / PUU-XIII / 2015. The purpose of this study was to describe the role of the notary in the deed Mating Agreement and its implementation after the decision of the Court in question, and to know the legal implications of the couples in mixed marriages. The method in this research is juridical empirical research methods.Keywords: Mating Agreement; Marriage Commingling; Deed; Decision of the Constitutional Court; Marriage Act.